BURST BLASTING: Solution to a Particular Blasting Problem - Wilfrid Comeau (International Society of Explosives Engineers, 2007)
Vibrograms, which last significantly longer than the actual blast (say 10 to 15 cycles or more), may be signalling an elastic response, which is not uniquely blast related. For example, geophones mounted on a part of a structure, which can elastically resonate at a frequency included in the seismogram, may not show the structure’s real reaction to the blast. This resonance usually amplifies the ground vibration. This contribution examines one particular case where blasting excited and amplified a resonant ground response, and the method used to significantly reduce or eliminate this undesirable condition.